CORPORATE RESOURCE MANAGEMENT SYSTEM OF BUSINESS PROJECTS UNDER THE SUSTAINABLE DEVELOPMENT CONDITIONS - Zybareva, Oksana V.; Shylepnytskyi, Pavlo; Белей (Belei), Cвітлана (Svitlana); Korzhenivska, Nataliya; Kravchuk, Iryna (Vytautas Magnus University Agriculture Academy, 2024)
In the article, the main theoretical aspects of the functioning of the corporate resource management system of business projects under the conditions of sustainable development are examined. The purpose of the article is to improve the existing approaches to the project resource management based on sustainable development in the conditions of the formation and functioning of the corporate project management system. The main approaches to the implementation of the corporate resource management system of business projects are considered. The stages of development of the corporate project resource management system have been determined. The main components of the corporate resource management system of business projects are substantiated. The task of integrating the methodology of the project management and the sustainable development concept at the level of business structures was determined, the consideration of the sustainable development aspects in the existing standards of the project management was investigated. The components of the project resource management system that require adaptation to the sustainable development goals are highlighted. To assess the economic, social and environmental efficiency of business projects in the context of the sustainable development principles, a system of the project selection criteria is proposed. The method of evaluation and selection of a rational business project based on the sustainable development principles is proposed.
CORPORATE RESOURCE MANAGEMENT SYSTEM OF BUSINESS PROJECTS UNDER THE SUSTAINABLE DEVELOPMENT CONDITIONS
Keywords: business structure, corporate management system, project, project management, sustainable development